Aplicación de ejercicios sensoriales para fortalecer el desarrollo integral de los estudiantes no videntes de la unidad educativa especializada de No Videntes de Cotopaxi, provincia de Cotopaxi, cantón Latacunga, parroquia La Matriz, periodo lectivo 2014-2015 - Morales Figueroa, Beatriz Margoth (2015)
The present research work determined the sensory exercises importance; themselves that helped to strengthen the integral development of the senses with the application of different activities in the blind people school Cotopaxi. We could check the knowledge lack from parents to apply sensory exercises at the same blind sons who helped develop the cognitive, socio-affective, language and motor areas. The repudiation of the sensorial exercises and the stimuli lack have produced that children have difficulty in recognizing shapes, sizes, colors, volume, textures, among others, which are essential in the abilities development and skills acquisition. Since, there is a shortage of didactic material, it is creating repetitive and isolated children who will not reach to develop their sensory skills into the teaching-learning processes, also, they contribute that the children during their early childhood develop whole, its potentialities through the senses use. They are applied in the research different sensory exercises was achieved to increase the integral development, the same that helped improve their senses and thus to enhance the teaching-learning process in the blind children.